Investigasi Tantangan dalam Penerapan Tata Kelola Keamanan Informasi di Sektor-Sektor Utama: Analisis Komparatif Lintas Negara - Saraswati, Karisa; Purwandari, Betty; Trisnawaty, Ni Wayan (AI Society & STMIK Indonesia, 2025)
This study investigates the challenges of implementing information security governance across countries. Initial analysis was carried out from cases in Indonesian organizations. Using Kitchenham’s systematic literature review to identify challenges and information security governance expert interviews to validate the result, the research analyzes thirty-four issues and compares them with those in other developing and developed countries. The objective is to identify common challenges, highlight differences, and propose recommendations for improvement. Findings reveal that Indonesia faces difficulties that are similar to those of other developing nations, such as limited leadership support and resource constraints. In contrast, developed countries struggle with overlapping regulations and maintaining compliance despite having stronger frameworks. The study emphasizes the importance of cohesive frameworks, enhanced training, and management support to improve governance practices. These results provide actionable insights for policymakers and organizations to strengthen information security governance and address the increasing complexity of global cybersecurity challenges.